Regular and Irregular Verb Mastery In Recount Text by Using Online Flashcard - Danar Cristanto; Armeria Wijaya; Listya Dewi Damajanti (PROCEEDING UMSURABAYA, 2026)
Learning English as Foreign Language is quite challenging for English Young Learner (EYL). One of the most important as fundamental skill is recognizing verb (Language Acquisition) as part of grammatical. Student must be able to differ the kind of Verb, is it Regular or Irregular?. This transformation quite simple but need attention from teacher. The successful of student writing skill depend on their understanding of this area. The application from this skill can be anywhere, Recount text as the example of application of Regular or Irregular Verb is the basic practice for them. Many ways to improve student mastery of this skill, the simply media teacher can try is by using digital method. At this moment, Researcher would like to apply online flashcard as method to improve student mastery of Regular and Irregular Verb. Before it begins, Researcher needs to have student competency to understanding their capacity. It is interesting to engage student attention by using digital media, because common media is less interesting today.